ANALYSIS OF TRANSPORT NETWORKS AND ROAD TRANSPORT ORGANIZATION IN EUROPEAN COUNTRIES - Nesterenko, H. I.; Muzykin, M. I.; Bibik, S. I.; Shvaiko A. Yu., Shvaiko A. Yu. (Systems and Technologies, 2023)
This article is devoted to the analysis of transport networks of such European countries as Slovakia, the Czech Republic and Poland and is of an overview nature. The article may be useful for refugees from Ukraine who crossed the border with these countries on their own transport, as well as for organizations engaged in mass transportation of people between Ukraine and the specified countries The article analyzes the organization of automobile traffic in these countries. In particular, standard speed limits, the total length of highways, the cost of fuel and travel on toll roads are defined. In addition, the amount of standard fines and the availability of mandatory car equipment in these countries were determined. The analysis of the organization of road traffic in Slovakia, the Czech Republic and Poland is presented in the form of tables and diagrams, on the basis of which conclusions were drawn about the possibility of further development of the system of organization of road traffic. Diagrams of speed limits, the length of the highway network, and the cost of fuel have been constructed. General maps of highways and maps of toll areas in each country are given. Similarities and differences in the three countries according to the given characteristics have been established. The conclusion summarizes the results regarding which of the countries is the most attractive for the organization of international transportation. A fee (electronic vignette) is provided for the use of limited sections of motorways and expressways in Slovakia by motor vehicles of foreign countries. The amount of the fee is related to the duration of use of the highways, regardless of the distance traveled or the number of trips. Parking in the city center is possible only in certain areas. Parking tickets are used in large cities. Parking machines (parkovacíautomaty) are used in most Czech cities. Payment is made in cash. Permissible parking time is from 30 minutes to 6 hours. The estimated cost depends on the location and ranges from 1.6-3.2 euros per hour. The length of the network of public roads in Poland is 423,997 km. Of them, 292,134 km are paved roads. The length of highways (Autostrady, marked with the letter A) is 1706 km. In Poland, there is a toll for the use of highways depending on the distance traveled. Poland has the most developed road network, because it has the largest length of all roads, paved roads and highways.